A Novel Cr2O3/MnO2-x Electrode for Lithium-Oxygen Batteries with Low Charge Voltage and High Energy Efficiency - Wei, Zhaohuan; Zhang, Zhiyuan; Ren, Yaqi; Zhao, Hong (Frontiers in Chemistry, 2021)
A high energy efficiency, low charging voltage cathode is of great significance for the development of non-aqueous lithium-oxygen batteries. Non-stoichiometric manganese dioxide (MnO2-x) and chromium trioxide (Cr2O3) are known to have good catalytic activities for the discharging and charging processes, respectively. In this work, we prepared a cathode based on Cr2O3 decorated MnO2-x nanosheets via a simple anodic electrodeposition-electrostatic adsorption-calcination process. This combined fabrication process allowed the simultaneous introduction of abundant oxygen vacancies and trivalent manganese into the MnO2-x nanosheets, with a uniform load of a small amount of Cr2O3 on the surface of the MnO2-x nanosheets. Therefore, the Cr2O3/MnO2-x electrode exhibited a high catalytic effect for both discharging and charging, while providing high energy efficiency and low charge voltage. Experimental results show that the as-prepared Cr2O3/MnO2-x cathode could provide a specific capacity of 6779 mAh g-1 with a terminal charge voltage of 3.84 V, and energy efficiency of 78 %, at a current density of 200 mA g-1. The Cr2O3/MnO2-x electrode also showed good rate capability and cycle stability. All the results suggest that the as-prepared Cr2O3/MnO2-x nanosheet electrode has great prospects in non-aqueous lithium-oxygen batteries.